Integrating Local Wisdom: Rapa'i Puloet Geurimpeng into an Articulated, Storyline-Based Learning Media to Enhance the Learning Motivation of Junior High School Students in Bireuen Regency - Ayu Jauhari; Indar Sabri; Trisakti (Journal of Practice Learning and Educational Development, 2026)
This study aims to develop an instructional media based on Articulate Storyline that integrates Acehnese local wisdom into the material on Rapa’i Puloet Geurimpheng arts to enhance the motivation of junior high school students. The research employs a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. The study was conducted at UPTD SMP Negeri 1 Bireuen, UPTD SMP Negeri 3 Bireuen, and UPTD SMP Negeri 4 Bireuen during the even semester of the 2025/2026 academic year, with the research subjects comprising 30 eighth-grade students, 2 media experts, 2 material experts, and 2 language experts. Data collection techniques included observation, interviews, questionnaires, and documentation. Data analysis was performed both quantitatively and qualitatively using percentage analysis, N-Gain, and Paired Sample T-Test with the assistance of SPSS software. The results indicate that the Articulate Storyline-based learning media is categorised as highly feasible based on validation from media, material, and language experts. The trial results show that teachers’ and students’ responses fall into the very good category. Furthermore, the product’s effectiveness results demonstrate an increase in students’ learning motivation after using the media, evidenced by improvements in pretest and posttest scores, N-Gain results in the moderate to high category, and statistical test results showing a significance value of less than 0.05. This study concludes that Articulate Storyline-based learning media, which integrates Acehnese local wisdom, is effective for use in Junior High School Arts and Culture lessons, as it can enhance students’ motivation and support the preservation of Acehnese local culture, particularly in Bireuen district.